Smart Educenter with Let’s Read Application for Children in Wonopuro Village - Endang Sri Maruti; Binti Isticomah; Galuh Mei Yustiwa; Ulifa Khoiru; Nur Huda (Nusantara Science and Technology Proceedings, 2021)
Wonopura village is a village located in the hills of Rajakwesi, Dukuh Sidowayah RT.11 RW.03 Sidoharjo Village, Jambon Ponorogo District which is quite remote. The lack of the role of the family and the environment, both schools and the surrounding community is a source of problems for children, especially related to literacy problems. This program aims to help children to improve their digital literacy skills and also make it easier for parents to guide and monitor their children's activities. For this reason, this program is carried out as an effort for Digital Education and Literacy for isolated village children so that they can continue to live life like children in other villages. This program is carried out for 1 month with four meetings on Sundays. Every meeting, gather the children in Wonopuro Village RT.11 RW.03 Dukuh Sidowayah, Sidoharjo Village, Jambon District, Ponorogo Regency. The result of the implementation of this program is that it can improve digital literacy for the children of Kampung Wonopuro. The increase can be seen from the social side, namely increasing children's enthusiasm for learning to develop their potential and achievements during the current pandemic conditions; from an economic point of view, it can increase the attractiveness of the outside community after knowing that Wonopuro Village is to be a regional tourist destination with beautiful natural scenery through ecoliteracy and ecotourism; and from a psychological point of view, it can help increase the learning motivation of the children of Kampung Wonopuro.